2020
DOI: 10.3390/insects11090564
|View full text |Cite
|
Sign up to set email alerts
|

Egg Sterilisation of Irradiated Nezara viridula (Hemiptera: Pentatomidae)

Abstract: Nezara viridula Linnaeus (Hemiptera: Pentatomidae) is a polyphagous pest of a wide range of economically important crops. Because the control of this species and other pentatomids relies primarily on insecticide application, investigation into the Sterile Insect Technique (SIT) is warranted. We aimed to investigate the irradiation biology of N. viridula for the potential application of SIT against this pest. Male and female N. viridula were gamma-irradiated at doses between 4 and 28 Gy and mated with both irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…However, this "alternative" procedure may be challenging both at the application and regulatory level. Interestingly, and similar to the abovementioned study on H. halys, Horrocks and colleagues (2020) [23] show that the application of an irradiation dose of 16 Gy or higher could sterilize male green vegetable bug Nezara viridula, another hemipteran species, by >99%, while females required a dose of 28 Gy to become fully sterile.…”
Section: Hemipterasupporting
confidence: 56%
“…However, this "alternative" procedure may be challenging both at the application and regulatory level. Interestingly, and similar to the abovementioned study on H. halys, Horrocks and colleagues (2020) [23] show that the application of an irradiation dose of 16 Gy or higher could sterilize male green vegetable bug Nezara viridula, another hemipteran species, by >99%, while females required a dose of 28 Gy to become fully sterile.…”
Section: Hemipterasupporting
confidence: 56%
“…This should be kept to a minimum in order to preserve the insect's behavior. Laboratory studies on three experimental groups of tsetse fly flies at completely different doses (60Gy, 80Gy, 100Gy, and 120Gy) on mated fertile females revealed that the number of aborted eggs/larvae was directly proportional to the dose [3,11].…”
Section: Methods Of Insect Sterilizationmentioning
confidence: 99%
“…Comparison the effect controlling mechanism of gamma radiation both at pupa and larva stage [3,11]. When we compared the average dose rate of pupa with adult insect which more easily controlled than that of pupa stage.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations